2019
DOI: 10.1016/j.jaci.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Allergic conversion of protective mucosal immunity against nasal bacteria in patients with chronic rhinosinusitis with nasal polyposis

Abstract: In patients with CRSwNP, nasal bacteria-reactive B cells differentiate into IgE-producing B cells through IgG/IgA-IgE class switching, suggesting that allergic conversion of the mucosal response against nasal bacteria underlies disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
0
32
0
2
Order By: Relevance
“…16 Local IgE class switching by B cells and IgE production is well documented in tissue from patients with CRSwNP. [17][18][19] Within the sinonasal mucosa, Staphylococcal enterotoxin-specific IgE and polyclonal IgE for inhalant allergens, as well as colonization by microbial agents including Staphylococcus aureus, are associated with CRSwNP irrespective of atopic status. 20 Locally produced IgE appears to be functional and involved in regulating chronic inflammation.…”
mentioning
confidence: 99%
“…16 Local IgE class switching by B cells and IgE production is well documented in tissue from patients with CRSwNP. [17][18][19] Within the sinonasal mucosa, Staphylococcal enterotoxin-specific IgE and polyclonal IgE for inhalant allergens, as well as colonization by microbial agents including Staphylococcus aureus, are associated with CRSwNP irrespective of atopic status. 20 Locally produced IgE appears to be functional and involved in regulating chronic inflammation.…”
mentioning
confidence: 99%
“…However, previous studies only detected the immunoreaction to Staphylococcus aureus in a small portion of Chinese patients with CRSwNP, even in eosinophilic type, disfavoring a role of Staphylococcus aureus in inducing IgE in Chinese patients (8,17,18) . Very recently, IgE antibodies against Streptococcus pyogenes and Haemophilus influenzae were detected and reported in Japanese patients with eosinophilic CRSwNP (19) . Therefore, the role of bacteria or common aeroallergens in the change of local IgE in NPs deserves further studies.…”
Section: Discussionmentioning
confidence: 99%
“…32,39 Increased mucosal infiltration of B cells, particularly germinal center B cells, and the presence of markers of class-switch recombination to IgE including epsilon germinal gene transcripts and epsilon circle transcripts in nasal polyps, strongly suggest local class-switch recombination to IgE in patients with eosinophilic CRSwNP. 3941 Tfh cells classically locate in germinal centers in secondary lymphoid tissues and play a crucial role in regulating B-cell responses. A recent study by Song et al demonstrated that the formation of ectopic lymphoid tissues was more frequently observed in nasal polyps and Tfh cells resided in these structures in polyps (Fig 1).…”
Section: Immune Polarization In Crsmentioning
confidence: 99%
“…39 Recently, by characterizing single cell-derived monoclonal antibodies, Takeda et al discovered that about 20% of isolated IgE antibodies recognized nasal bacteria such as Staphylococcus aureus , Streptococcus pyogenes , and Haemophilus influenza . 41 …”
Section: Immune Polarization In Crsmentioning
confidence: 99%